Gender Stereotypes in Advertising - Kniazian, Anna (Armenian Folia Anglistika, 2014)
The portrayal of men and women in advertising has received conside rable atten - tion over the last several decades, both by practitioners and academics. Research has primarily focused on the visual portrayal of men and women in advertising, within the realm of which, there appears to be a fundamental difference in the way men and women are portrayed. Men are generally stereotyped as competent, assertive, independent, and achievement oriented, whereas women are generally stereotyped as warm, sociable, interdependent, and relationship-oriented. Women are more often portrayed as young and concerned with physical attractiveness than their male counterparts. Masculine and feminine stereotypes are complementary in the sense that each gender group is seen as possessing a set of strengths that balance out their own weaknesses and that supplement the assumed strengths of the other group.
Keywords: gender advertising; gender roles; masculine and feminine stereotypes in TV advertising